1983
DOI: 10.1111/j.1471-4159.1983.tb13562.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Uptake and Release in the Presence of Glucose by Sympathetic Ganglia of Chicken Embryos and by Neuronal and Nonneuronal Cultures Prepared from These Ganglia

Abstract: Uptake and output of lactate were measured in lumbar sympathetic chains excised from embryos of white leghorn chickens, 14-15 days old. The chains, typically containing 30-40 micrograms of protein, were incubated in Eagle's minimum essential medium containing bicarbonate buffer, 6-17 mM glucose, various concentrations of lactate, and either [U-14C]lactate, [1-14C]glucose, or [6-14C]glucose. The average rate of uptake of labeled lactate was measured with incubations of 5-6 h, starting with various external lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
44
1
1

Year Published

1988
1988
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 32 publications
3
44
1
1
Order By: Relevance
“…The value found for the apparent K m of lactate transport is slightly smaller than that found for sympathetic ganglia in vitro (2.4 vs. 4.8 mM; Larrabee, 1983). This is very encouraging, since diffusional processes are likely only to impede the apparent kinetics (i.e., increase K m or decrease V max) .…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The value found for the apparent K m of lactate transport is slightly smaller than that found for sympathetic ganglia in vitro (2.4 vs. 4.8 mM; Larrabee, 1983). This is very encouraging, since diffusional processes are likely only to impede the apparent kinetics (i.e., increase K m or decrease V max) .…”
Section: Discussionmentioning
confidence: 49%
“…The use of a kinetic model for reversible lactate transport across the cell membrane was prompted by the observation that lactate levels always re turned to a steady-state value of � 1.1 mM in ECF after electroconvulsive shock or chemical stimula tion (Kuhr and Korf, 1988b). Larrabee (1983) has demonstrated similar behavior for lactate transport in sympathetic ganglia in vitro. This transport was saturable and showed distinct characteristics of an equilibrium system-there was a consistent ap proach to the same steady-state level, regardless of whether initial extracellular levels were higher or lower than final steady-state values.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The model asserts that astrocytes contain glycogen, which is converted into lactate for transport to axons during glucose deprivation. Lactate is the most likely fuel to be transferred from astrocytes to axons for the following reasons: (1) astrocytes, but not neurons, are known to extrude large amounts of lactate (Walz and Mukerji, 1990); (2) astrocytes, but not neurons, can survive for a limited time on anaerobic metabolism alone (Goldberg and Choi, 1993;Pappas and Ransom, 1995;Ransom and Fern, 1996) and could "afford" to export large amounts of lactate; (3) lactate, but not glucose, is released from astrocytes when glucose is removed (Dringen et al, 1993); (4) lactate has been shown to be an effective fuel in numerous types of CNS tissue (Larrabee, 1983;Schurr et al, 1988;Izumi et al, 1994;Izumi et al, 1997), including RON axons (Wender et al, 1999); (5) lactate from Müller cells fuels photoreceptors in guinea pig retina (Poitry-Yamate et al, 1995). According to the model, axons import lactate for subsequent oxidative metabolism to generate ATP.…”
Section: Discussionmentioning
confidence: 99%
“…Although glucose is the preferred substrate for brain and retina, there is accumulating evidence that lactate is an alternative substrate for energy metabolism in vertebrate nervous tissues (see, e.g., Larrabee 1983Larrabee , 1992Schurr et al, 1988). Recent evidence additionally points to the possibility of a cellular compartmentation of lactate metabolism and its trafficking from astroglia to neurones McKenna et al, 1993;Wiesinger et al, 1993;Pellerin and Magistretti, 1994).…”
mentioning
confidence: 99%